2021
DOI: 10.1128/aem.01110-21
|View full text |Cite
|
Sign up to set email alerts
|

Viable but Nonculturable State of Yeast Candida sp. Strain LN1 Induced by High Phenol Concentrations

Abstract: Microbial degradation plays an important role in the environmental remediation. However, most microorganisms’ pollutant-degrading capability is weakened due to their entry into a viable but non-culturable (VBNC) state. Despite there is some evidence for the VBNC state of pollutant-degrading bacteria, limited studies have been conducted to investigate the VBNC state of pollutant degraders among fungi. In this work, the morphological, physiological and molecular changes of a phenol-degrading yeast strain LN1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Carbohydrates are the most important constituents for discriminating between cell states, and they are the energy source used to maintain cell activity [ 44 ]. The variation in Raman peaks attributed to carbohydrates was analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrates are the most important constituents for discriminating between cell states, and they are the energy source used to maintain cell activity [ 44 ]. The variation in Raman peaks attributed to carbohydrates was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports found that several genes involved in carbohydrate and energy metabolism in yeast and bacteria were downregulated in the VBNC state [ 12 , 45 ]. However, different stress conditions and microbial species exhibited different changes in their carbohydrate metabolism [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, there was no significant difference in biomass between the two group. Many functional microbial populations enter viable but non-culturable (VBNC) state ( Xie et al, 2021 ) under unfavorable conditions to deal with environmental stresses, including oligotrophic nutrients and high concentration of pollutants ( Su et al, 2021 ). Under the conditions of NAP or/and PHE as carbon sources, SL-6 didn’t show an obvious growth comparing to growing on LB ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These properties of VBNC cells are more important in determining their potential influence on human health, as their resistance to harsh environments allows them to remain viable during transport over long distances . Although there have been several reports of fungi being found in the VBNC state, VBNC cells generally refer to bacteria. Li et al (2014) identified 51 human pathogens capable of existing in the VBNC state, suggesting that numerous other microorganisms may have the same pattern of physiological activity . Notably, Legionella bacteria, which enter the VBNC state under conditions of nutritional deficiency, have been found to maintain infectivity for over a year .…”
Section: Factors Influencing Bioaerosol Infectivitymentioning
confidence: 99%